An ESP Project of Authentic Scholarship Essays by L2 Vocational Students - Ningrum, Sulistya; Zakaria (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2023)
This study investigated an English for Specific Purposes (ESP) project centered on authentic scholarship essays created by English as a Second Language (ESL) vocational learners. The project aligned with ESP principles, emphasizing tailored language instruction to meet learners’ communicative needs and genre-specific language skill development. Scholarship essays, authored by ESL learners, represent a nexus of linguistic diversity and academic achievement, offering insights into their language proficiency development. The study explored the linguistic challenges faced by ESL learners in composing scholarship essays within vocational settings. Evaluating project-based outcomes, the research sheds light on the difficulties students encounter in self-assessment, coherence, punctuation usage, and conveying enthusiasm. The findings underscored the importance of a scaffolded approach, providing guidelines, exemplars, and targeted feedback to enhance authentic self-assessment and writing proficiency. The study contributed to understanding the role of ESP projects in developing discipline-specific language skills among vocational students and informs strategies for effective scholarship essay composition in ESL settings.